Hydrolysis of Organophosphate: Reaction Mechanism of 2,4,6-Trichloroaniline Phosphoro Triamidate via Conjugate Acid Species - R.K. Choursia, Nimisha; Bhadoria, A.K.S.; Shivhare, R.L. (Asian Journal of Chemistry, 2010)
2,4,6-Trichloroaniline phosphoro triarnidate undergoes hydrolysis in acidic medium ranging from 1 M HCl to 6 M HCl. The product of hydrolysis increases with increasing temperature and time until 4 M acid value and then decreases afterwards. The parameters such as substrate concentration and Arrhenius parameter have also been studied. The linear curves of Arrhenius parameter reflect the uniformity of the reaction. The influence of the nature of reactive species is determined by the study of ionic strength. Further, tire study of solvent effect indicates the formation of transitional state, during hydrolysis. Bunnett-Olsen parameter suggests that water is not involved in the rate determining step of the reaction.